Reverberations of revolution transnational perspectives, 1770-1850 - Amann, Elizabeth; Boyden, Michael (Edinburgh critical studies in Atlantic literatures and cultures, 2021)
A broad, comparative and trans-Atlantic approach to the Age of Revolution.